2010
DOI: 10.1055/s-0029-1245199
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Intraocular Pressure Increase and Glaucoma Prevalence in Thyroid Eye Disease: A Mini-Review

Abstract: In TED, glaucoma prevalence does not seem to be significantly increased and, from a pathophysiological standpoint, the long-term IOP increase is essentially due to episcleral venous pressure elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 5 publications
2
13
0
1
Order By: Relevance
“…The data on previous treatments for GO prior to referral are encouraging, suggesting that non-specialised centres tend to leave decisions for eye surgery to tertiary centres though this did not hold true for medical therapies. The explanation for a lower prevalence of glaucoma in the 2012 than the 2000 cohort is unclear, but may be due to better appreciation that raised intraocular pressure in patients with GO does not equate to glaucoma 12. The prevalence of glaucoma in the 2012 cohort (5.6%) is similar to other published data on prevalence of glaucoma in GO 13.…”
Section: Discussionsupporting
confidence: 70%
“…The data on previous treatments for GO prior to referral are encouraging, suggesting that non-specialised centres tend to leave decisions for eye surgery to tertiary centres though this did not hold true for medical therapies. The explanation for a lower prevalence of glaucoma in the 2012 than the 2000 cohort is unclear, but may be due to better appreciation that raised intraocular pressure in patients with GO does not equate to glaucoma 12. The prevalence of glaucoma in the 2012 cohort (5.6%) is similar to other published data on prevalence of glaucoma in GO 13.…”
Section: Discussionsupporting
confidence: 70%
“…The ocular complaint was observed in 44.27% of patients; foreign body sensation being the most common presenting symptoms in 61.79%. In a study done by Kashkouli et al, bilateral proptosis (9.9%), burning sensation (5.4%), pain behind the eye (5.3%), and puffiness (4.7%) were the most common signs and symptoms [13]. The frequency of in the present study is 67% of have common symptoms.…”
Section: Original Research Articlesupporting
confidence: 55%
“…In a study by Haefliger et al, performed on 500 patient charts, the prevalence of increased IOP was noted to be 24% [13]. In 2007, Behrouzi et al reported a prevalence of 11%, and He reported an incidence of 31.3% in Chinese patients [14].…”
Section: Discussionmentioning
confidence: 98%
“…Adjusted for other risk factors, they reported that OAG did not show significant association with hypothyroidism. Haefliger et al [32] said that glaucoma prevalence does not seem to be significantly increased in thyroid eye disease. Kakigi et al [33] reported a similar result with us.…”
Section: Discussionmentioning
confidence: 99%